A comparative study on high pulse energy femtosecond laser drilling of high-aspect-ratio holes under different pressure conditions. (6th January 2023) - Wang, Rujia; Wang, Kedian; Fan, Zhengjie; Sun, Xiaomao; Dong, Xia; Mei, Xuesong; Zhang, Wenwu
Abstract: Laser drilling of high-aspect-ratio holes is gradually on the agenda in the field of aerospace manufacturing. We present a comparative study of high pulse energy femtosecond laser micro-hole machining of thermal barrier coated superalloys under different pressure conditions. The ablation results showed that severe contaminative ablation patterns occurred near the geometric focus position, which is related to the remarkable refraction of the plasma near the geometric focus. Adopting negative defocus positions can restrain the plasma defocusing effect and eliminate these ablation defects. As compared to the case in the atmospheric pressure condition, the drilled holes had good retention in diameters, and the aperture size as small as 30 μm can be achieved in the low-pressure environment, which is attributed to a good suppression of the plasma defocusing effect. The drilled samples have convergent and divergent shapes struck within the hole in the low-pressure condition while the hole profiles show good collimation along the thickness direction in the atmospheric pressure environment. This can be attributed to the fact that the pulse energy can be well dispersed to the hole sidewall because of the plasma defocusing effect in the atmospheric pressure environment, and the sidewall materials can be effectively removed. The maximum aspect ratio of the hole can reach 15.7 based on the drilling results. The presented results provide some guidance for the machining of micro-holes with high aspect ratios on other occasions. Highlights: Severe contaminative ablation occurred near the geometric focus position. Processing at negative defocus positions can be adopted to minimize the plasma defocusing effect. The aperture size as small as 30 μm can be achieved in a low-pressure environment. The pulse energy can be well dispersed to the hole sidewall in the atmospheric environment.